2020
DOI: 10.1016/j.cytogfr.2020.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Are we fully exploiting type I Interferons in today's fight against COVID-19 pandemic?

Abstract: Coronavirus disease 2019 (COVID-19) first emerged in late 2019 in China. At the time of writing, its causative agent SARS-CoV-2 has spread worldwide infecting over 9 million individuals and causing more than 460,000 deaths. In the absence of vaccines, we are facing the dramatic challenge of controlling COVID-19 pandemic. Among currently available drugs, type I Interferons (IFN-I)-mainly IFN-α and β-represent ideal candidates given their direct and immune-mediated antiviral effects and the long record of clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 62 publications
(75 reference statements)
0
26
0
Order By: Relevance
“…While today IFN-I have been largely replaced by new drugs in the clinical practice in patients with cancer and viral or autoimmune diseases, the most recent knowledge on the complex roles of these cytokines under different pathologic conditions reveals new and more selective strategies for their clinical use [ 23 , 116 ]. Novel and potentially more effective modalities of using these cytokines should take into account the IFN effects on cell metabolism at different tissue levels and under various physiological conditions, including hyperglycemia and obesity.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…While today IFN-I have been largely replaced by new drugs in the clinical practice in patients with cancer and viral or autoimmune diseases, the most recent knowledge on the complex roles of these cytokines under different pathologic conditions reveals new and more selective strategies for their clinical use [ 23 , 116 ]. Novel and potentially more effective modalities of using these cytokines should take into account the IFN effects on cell metabolism at different tissue levels and under various physiological conditions, including hyperglycemia and obesity.…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…Although the use of the pulmonary route represents an asset in terms of therapeutic precision, lack of knowledge of IFN nebulization remains a major limitation (Aricò et al, 2020). In order to apply this therapeutic modality to COVID-19, we explored the possibility of nebulizing IFN-β-1b.…”
Section: Discussionmentioning
confidence: 99%
“…This limit was also highlighted by Jalkanen et al, who suggested to use the parenteral route in order to achieve more efficacious concentrations (Jalkanen et al, 2020). Higher, more specifically pulmonary concentrations could be obtained with inhaled IFN, but available pharmaceutical forms and pharmacokinetic data on this method of administration remain limited in the Western world (Aricò et al, 2020).…”
Section: Toward the Use Of Type I Interferon Via Inhalationmentioning
confidence: 99%
“…The associated diseased condition was termed COVID-19 by the World Health Organization (WHO) [ 1 ]. The WHO announced SARS-CoV-2 virus infection a pandemic as it infected nearly 9 million persons, and engulfed more than 460,000 worldwide [ 2 ]. SARS-CoV-2 is a member of β coronaviruses, consisting of ∼30 kb single-stranded positive-sense RNA as genetic material [ 3 ].…”
Section: Introductionmentioning
confidence: 99%